Effect of new type extrusion modification technology on supramolecular structure and in vitro glycemic release characteristics of starches with various estimated glycemic indices - Li, Bo; Zhang, Yanjun; Luo, Wanru; Liu, Jin; Huang, Chongxing (Frontiers in Nutrition, 2022)
Nowadays, the highly effective modified technology to starch with various digestibility is gaining interest in food science. Here, the interactions between glycemic release characteristics and fine supramolecular structure of cassava (ECS), potato (EPS), jackfruit seed (EJFSS), maize (EMS), wheat (EWS), and rice starches (ERS) prepared with improved extrusion modification technology (IEMS) were investigated. The crystalline structures of all extruded cooking starches changed from the A-type to V-type. IEMS-treated cassava, potato, and rice starches had broken α-1.6-glycosidic amylopectin (long chains). The others sheared α-1.4-glycosidic amylopectin. The molecular weight, medium and long chain counts, and relative crystallinity decreased, whereas the number of amylopectin short chains increased. The glycemic index (GI) and digestive speed rate constant (k) of ECS, EPS, EJFSS, and EWS were improved compared to those of raw starch. Although EMS and ERS had degraded molecular structures, their particle morphology changed from looser polyhedral to more compact with less enzymolysis channels due to the rearrangement of side chain clusters of amylopectin, leading to enzyme resistance. The starch characteristics of IEMS-treated samples significantly differed. EPS had the highest amylose content, medium chains, long chains, and molecular weight but lowest GI, relative crystallinity, and k. ERS showed the opposite results. Thus, IEMS may affect starches with different GIs to varying degrees. In this investigation, we provide a basis for wider applications of conventional crop starch in the food industry corresponding to different nutrition audience.